Multiscale Evaluation of Recycled Plastic Corrugated Panels for Sustainable Construction - Aaroon Joshua Das; Majid Ali (Buildings)
The global push for sustainable building practices has intensified the search for low-carbon, recyclable alternatives to traditional roofing materials. This study investigated the structural viability of corrugated panels fabricated from 100% post-consumer recycled HDPE and PP for roofing and cladding applications under real-world loading and environmental conditions. Promising main attributes include durability, corrosion resistance, and low environmental impact. Mechanical testing revealed a flexural strength of 8.4 MPa for rHDPE and 6.3 MPa for rPP. Under impact loading, rPP retained 53% of its initial strength, while rHDPE retained 28%, as validated by drop-weight and pendulum impact tests. Vibration testing (ASTM E1876) demonstrated that rPP exhibited 18% higher longitudinal damping, whereas rHDPE outperformed in out-of-plane vibration control. XRD and SEM-EDS confirmed distinct crystalline and morphological structures responsible for the observed behavior. Findings from this investigation, supported by prototype slab testing, confirm that integrating recycled plastics facilitates the creation of durable and sustainable building envelopes for circular construction practices.